DNA-LAUNCHED INFECTIOUS CLONE WITH AN ARTIFICIAL INTRON: INFLUENCE ON VIRUS RESCUE AND GROWTH - Keyer, V.V.; Syzdykova , L.R.; Shevtsov , A.B.; Shustov , A.V. (Eurasian Journal of Applied Biotechnology, 2019)
A DNA-launched infectious clone is a plasmid that contains the full-genome cDNA copy of a viral genome under control of a eukaryotic promoter. Transfection of the plasmid in cell culture can then rescue the virus and allow for its growth. In this study, DNA-launched infectious clones of Venezuelan equine encephalitis virus (VEE) were produced. In the developed constructs, a cDNA copy of the VEE genome was placed under control of the cytomegalovirus (CMV) promoter, and a ribozyme and polyadenylation signal were engineered at the 3′-end of the sequence. Moreover, a small hybrid intron (composed from parts of the second beta-globin intron and the IgG intron) was cloned into the junction between the viral 5′-untranslated region (UTR) and the nsP2 gene, and the effects of inserting an intron in the DNA-launched infectious clone on the rescue efficiency and growth kinetics were assessed.The rescue efficiency was high for all constructs at 4.8 × 104 focus-forming units (FFU)/ mg of transfected plasmid DNA for the parental construct, 4.0 × 104 FFU/mg for the construct with a non-natural PstI site between the 5′UTR and nsP2 gene, and 1.0 × 104 FFU/mg for the construct with the intron placed in a selected genomic position. The three rescued viruses reached similar titers, indicating that the intron does not have a major effect on the rescuing efficiency. Thus, we have demonstrated an efficient method of cloning introns into natural or engineered PstI sites to achieve efficient viral rescue and growth.